Report of the United Nations Visiting Mission to the Trust Territory of the Pacific Islands, 1973, Together with the Relevant Resolution of the Trustship Council - United Nations, New York, NY. Trusteeship Council; United Nations, New York, NY. Trusteeship Council (Washington, D.C. : Distributed by ERIC Clearinghouse, 1973)
In 1973 the United Nations Trusteeship Council dispatched a visiting mission to the Trust Territory of the Pacific Islands which consists of three archipelagos: the Marshalls, the Carolines, and the Marianas. This publication contains a report of the mission which was comprised of representatives from the governments of Australia, France, the Union of Soviet Socialist Republics, Great Britain, and Northern Ireland. The itinerary, a short description of the land and the people visited, and the program of visits and meetings are followed by reports on the following topics: (1) Political Advancement, (2) Economic Advancement, (3) Social Advancement, (4) Educational Advancement, (5) War and Post-War Damage Claims, and (6) Culture Status. The annexes contain a list of written communications received by the visiting mission during its visit to the Trust Territory and Resolution 2159 adopted by the Trusteeship Council. (Author/RM)
Availability: United Nations, Sales Section, New York, New York 10017 (Document No. T/1748; $5.00).
ERIC Note: Trusteeship Council, Official Record: Fortieth Session (29 May-22 June 1973), Supplement No. 2.
Educational level discussed: Elementary Education.
Educational level discussed: Higher Education.
Educational level discussed: Secondary Education.
Microfiche.
Keywords: Comparative Education; Economic Development; Educational Development; Elementary Education; Foreign Culture; Futures (of Society); Government (Administrative Body); Higher Education; International Education; Politics; Reports; Secondary Education; Social Development; War; Pacific Trust Territory (Marshall Islands); Collected Works, Proceedings